A Study on the Washback Effects of the Test for English Majors (TEM) Implications for Testing and Teaching Reforms - Xu, Qian (Springer Singapore, 2018)
This book adopts a multi-method and multi-phase approach to investigate the washback effects of Test for English Majors (TEM) on program administrators, teachers and students, shedding new light on TEM reform and the reform of English teaching and learning in China. TEM, a nationwide test used to measure the language proficiency of undergraduate English majors in China, is a major standardized test taken by nearly 400,000 students every year. The book's key features include: an in-depth discussion of the nature of washback and a framework for investigating it; a multi-method and multi-phase approach, employing both the quantitative method of questionnaire surveys and the qualitative methods of interviews and classroom observations; large-scale questionnaire surveys conducted among experts, program administrators, teachers and students, and involving over 30,000 participants; detailed assessments of TEM's washback effects on stakeholders' perceptions, classroom teaching practice, students learning activities, etc.; and essential insights into testing and teaching reforms.